PELATIHAN PEMBUATAN KULTUR BAKTERI PROBIOTIK UNTUK UNTUK MENINGKATKAN PRODUKTIVITAS TAMBAK UDANG WINDU DI KABUPATEN BULUNGAN: Pelatihan Pembuatan Kultur Bakteri Probiotik untuk Meningkatkan Produktivitas Tambak Udang Windu - Amien, Muhammad; Mansyur, Nur Indah; Hasanah, Nurjannatul; Pratama, Seftian Sanju; Azizah, Adelina Nur; Fitri, Fitri; Sakinah, Nur; Nuryanti, Nuryanti; Ose, Anjelina Mariani (jsd: Journal of Society and Development, 2025)
Declining productivity in tiger shrimp aquaculture is often associated with unstable environmental quality and suboptimal pond management, making probiotics a promising environmentally friendly approach to improving water conditions, suppressing disease, and supporting shrimp growth. To enhance farmers’ capacity in utilizing probiotics, a community engagement program involving training and hands-on assistance in the preparation of probiotic bacterial cultures was conducted in July 2025 at Mitra Serumpun, Tarakan City. The activities were delivered through lectures, demonstrations, and guided practice that directly involved participants in the fermentation and culture preparation processes. Evaluation results indicated an increase in participants’ knowledge and skills related to probiotic fermentation techniques and their application in shrimp ponds. This program contributed to strengthening farmers’ readiness to optimize pond management and supported efforts to improve aquaculture productivity and local food security.